A specific small game exploitation for Lower Paleolithic: The beaver (Castor fiber) exploitation at the Caune de l'Arago (Pyrénées-Orientales, France). (February 2017) - Lebreton, Loïc; Moigne, Anne-Marie; Filoux, Arnaud; Perrenoud, Christian
Abstract: Beaver exploitation is little documented for the Lower Paleolithic, in the Caune de l'Arago (Tautavel, France) beaver remains are present in ten levels dated from the Middle Pleistocene. Levels Gs4 and J provide bones with cut-marks. These cut-marks are located on the long bones, indicating meat removal and also on the metapodials, indicating that the animals were skinned before defleshing. The few beaver remains in each level could lead us to think that its exploitation was opportunistic but the fact that this exploitation occurs in two levels shows that it was not an exceptional practice. Even if small game was proposed in addition to large mammal exploitation for the model of hominid subsistence, evidence is scarce for the Lower Paleolithic. Their exploitation, even occasional, shows that large mammals are not the only meat resource used in this site. Highlights: The Caune de l'Arago provide the first direct evidence of beaver exploitation by hominids ( H . erectus ). Human procurement and modifications are recorded in two different levels shows that it is not an exceptional practice Beaver exploitation in brings another evidence of the use (even if it is opportunistic) of small game